A novel equation that incorporates the linear and hyperbolic nature of the force-velocity relationship in lower and upper limb exercises - Alcazar, J.; Pareja-Blanco, F.; Rodriguez-Lopez, C.; Gutierrez-Reguero, H.; Sanchez-Valdepeñas, H.; Cornejo-Daza, P. J.; Ara,I.; Alegre, L. M. (European Journal of Applied Physiology, 2022)
The purpose of this study is to provide a force-velocity (F-V) equation that combines a linear and a hyperbolic region, and to compare its derived results to those obtained from linear equations. A total of 10 cross-training athletes and 14 recreationally resistance-trained young men were assessed in the unilateral leg press (LP) and bilateral bench press (BP) exercises, respectively. F-V data were recorded using a force plate and a linear encoder. Estimated maximum isometric force (F0), maximum muscle power (Pmax), and maximum unloaded velocity (V0) were calculated using a hybrid (linear and hyperbolic) equation and three different linear equations: one derived from the hybrid equation (linearhyb), one applied to data from 0 to 100% of F0 (linear0-100), and one applied to data from 45 to 100% of F0 (linear45-100). The hybrid equation presented the best fit to the recorded data (R2 = 0.996 and 0.998). Compared to the results derived from the hybrid equation in the LP, significant differences were observed in F0 derived from linear0-100; V0 derived from linearhyb, linear0-100 and linear45-100; and Pmax derived from linearhyb and linear45-100 (all p < 0.05). For the BP, compared to the hybrid equation, significant differences were found in F0 derived from linear0-100; and V0 and Pmax derived from linearhyb, linear0-100 and linear45-100 (all p < 0.05). An F-V equation combining a linear and a hyperbolic region showed to fit adequately recorded F-V data from ~ 20 to 100% of F0, and overcame the limitations shown by linear equations while providing relevant results.